2015
DOI: 10.1016/j.bjorl.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss assessment in primary and secondary acquired cholesteatoma

Abstract: There was association between hearing loss and the type of cholesteatoma. Secondary cholesteatoma resulted in greater hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…Our results seem to be according with the ones obtained from Olsen et al 43 which found an average loss of 50.86 (air threshold) and 50.34 dB for 2000 and 4000 Hz, respectively, in a secondary cholesteatoma. In Figure 11 we can see and average of 49.0 dB loss for the large cholesteatoma between the same range from 2000 to 4000 Hz, which is a close results comparing with the experimental values of the Olsen et al 43 research. The main difference is regarding the low frequencies between 500 and 1000 Hz where our results showed an average hearing loss of 16.01 dB for the large cholesteatoma, while the Olsen et al 43 research present the same 50 dB loss for low frequencies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results seem to be according with the ones obtained from Olsen et al 43 which found an average loss of 50.86 (air threshold) and 50.34 dB for 2000 and 4000 Hz, respectively, in a secondary cholesteatoma. In Figure 11 we can see and average of 49.0 dB loss for the large cholesteatoma between the same range from 2000 to 4000 Hz, which is a close results comparing with the experimental values of the Olsen et al 43 research. The main difference is regarding the low frequencies between 500 and 1000 Hz where our results showed an average hearing loss of 16.01 dB for the large cholesteatoma, while the Olsen et al 43 research present the same 50 dB loss for low frequencies.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the lack of consensus regarding the influence of a cholesteatoma in hearing loss among scientific community, the degradation of the ossicular chain seems to be frequent. Some level of ossicular degradation was found in more than 90% of the 80 cases analyzed in the work of Olsen et al 43 and around 83% in the 100 patients studied in the work of Khdim et al 10 One of the most recent works 10 that compare hearing loss in different cholesteatoma conditions showed an average loss of 54.1 dB in 80% of the evaluated cases, with the cholesteatoma placed in the antro attical location. Our results seem to be according with the ones obtained from Olsen et al 43 which found an average loss of 50.86 (air threshold) and 50.34 dB for 2000 and 4000 Hz, respectively, in a secondary cholesteatoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the conditions start with chronic otitis where otorrhea persists even after appropriate clinical treatments, resulting in changes to the middle ear that, over time, end up progressively compromising hearing. Secondary cholesteatoma causes greater hearing impairment than primary cholesteatoma, probably due to recurrent infections and erosion of the auditory ossicles 5 . This fact was evidenced in this clinical case by anacusis and labyrinthitis ossificans, with involvement of the labyrinth and cochlea, visualized on CT (Figure 2).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Cholesteatoma is a cystic pseudotumor located mostly in the middle ear, and less frequently in other areas of the temporal bone (1). Etiopathogenetically, it is regarded as a heterogeneous disease, where besides embryonic disorders (congenital cholesteatoma), there are other participating postnatal factors like epithelial metaplasia, retraction pocket and dysfunctional eustachian tube (acquired cholesteatoma) (2). Its wall, called matrix, consists of keratin producing squamous epithelium (3).…”
Section: Introductionmentioning
confidence: 99%